Learning language through task repetition - Bygate, Martin (Task-based language teaching : issues, research and practice (TBLT),, 2018)
"After more than 20 years of research, this is the first book-length treatment of second language task repetition - the repetition of encounters with a task that involve re-using the same content with the same overall purpose. The topic links task performance with the growing mastery of both the task and of relevant language, and constitutes a site with special potential to promote learning within and across language lessons, and for preparing students for assessment and of course real-world language performance. The volume assembles chapters that complement each other in interesting ways: significant background reviews, studies of patterns of change across task repetition iterations, and reports on the use and nature of task repetition in language classes in on-going programmes. Contributors draw on a variety of interpretive frameworks and report from a range of language educational contexts. The volume will be of interest to language researchers, teacher educators, teachers, and students, as well as others interested in the contribution of task repetition to learning"--